2020
DOI: 10.3390/e22070765
|View full text |Cite
|
Sign up to set email alerts
|

A Denoising Method for Fiber Optic Gyroscope Based on Variational Mode Decomposition and Beetle Swarm Antenna Search Algorithm

Abstract: Fiber optic gyroscope (FOG) is one of the important components of Inertial Navigation Systems (INS). In order to improve the accuracy of the INS, it is necessary to suppress the random error of the FOG signal. In this paper, a variational mode decomposition (VMD) denoising method based on beetle swarm antenna search (BSAS) algorithm is proposed to reduce the noise in FOG signal. Firstly, the BSAS algorithm is introduced in detail. Then, the permutation entropy of the band-limited intrinsic mode functions (BLIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…where a i is the Lagrange multiplier, and the Lagrangian function is used to derive the derivation w, b, ξ i , a i , respectively. The optimality condition of the KKT point is expressed in Equations ( 15)- (18).…”
Section: Gwo-lssvm Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…where a i is the Lagrange multiplier, and the Lagrangian function is used to derive the derivation w, b, ξ i , a i , respectively. The optimality condition of the KKT point is expressed in Equations ( 15)- (18).…”
Section: Gwo-lssvm Algorithmmentioning
confidence: 99%
“…The experimental results demonstrated that the novel method is superior to both the EMD-HRD and EMD-SFT approaches with a higher SNR ratio. Song et al [18,19] proposed a hybrid algorithm of an optimized local mean decomposition-kernel principal component analysis (OLMD-KPCA) method. The Allan variance analysis results indicated that the Q, N, and B reduced from 12.915 to 2.429 × 10 −1 , 1.8 × 10 −2 to 5.061 × 10 −4 , and 3.01 × 10 −1 to 1 × 10 −2 based on the X axis; from 7.680 to 1.38 × 10 −1 , 1.2 × 10 −2 to 2.647 × 10 −4 , and 1.72 × 10 −1 to 6 × 10 −3 based on the Y axis; and from 7.093 to 1.25 × 10 −1 , 1 × 10 −2 to Micromachines 2023, 14, 1712 3 of 18 1.549 × 10 −4 , and 1.53 × 10 −1 to 7 × 10 −3 based on the X axis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…proposed an improved VMD method based on the Beetle Antennae Search algorithm, where the kurtosis of intrinsic mode functions was used as the fitness function during the search process. 8 Gai et al. optimized VMD parameters using a hybrid Gray Wolf algorithm, significantly improving the optimization speed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intelligent optimization algorithms, as a new evolutionary computational tool, have been widely used in engineering optimization problems [2][3][4]. As one of the heuristic search algorithms, the Beetle Antennae Search (BAS) algorithm enjoys the advantages of fast convergence, simple model, low computational complexity, and robust searching ability [5,6], and is widely employed in several engineering optimization problems with high research value [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%